A 54-kDa protein overexpressed by chloroquine-resistant Plasmodium berghei ANKA strain - Li Gao-De; Qu Feng-Yi; Chen Xiong; Ni Can-Rong (Acta Pharmacologica Sinica, 2016)
Using an insoluble chloroquine-adsorbent, a 54-kDa protein (with a range of 50-60 kDa) was extracted from serum of mice infected with chloroquine-resistant (CR) Plasmodium berghei ANKA strain. Immunoblotting assay with antiserum against the 54-kDa protein showed that the content of the protein was higher in serum of mice infected with the CR parasites than that of mice infected with chloroquine-sensitive (CS) P berghei ANKA strain, and that instead of the 54-kDa protein, a set of 15-, 16-, and 23-kDa proteins was found to be highly overexpressed in lysate of purified CR parasites in comparison with that of purified CS parasites, suggesting the 54-kDa protein probably to be composed of 3 subunits. These findings may bear great importance in probing mechanism of chloroquine resistance in malaria parasites.